2017
DOI: 10.1371/journal.pone.0168233
|View full text |Cite
|
Sign up to set email alerts
|

PUMA and NF-kB Are Cell Signaling Predictors of Reovirus Oncolysis of Breast Cancer

Abstract: Background and purposeReovirus is a ubiquitous RNA virus that exploits aberrant signaling pathways for its replication. The oncolytic potential of reovirus against numerous cancers under pre-clinical/clinical conditions has been documented by us and others. Despite its proven clinical activity, the underlying mechanisms of reovirus oncolysis is still not well elucidated. If reovirus therapy is to be optimized for cancer, including breast cancer patients, it is imperative to understand the mechanisms of reoviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
(44 reference statements)
1
18
0
Order By: Relevance
“…We next explored the role of these seven lncRNAs and their corresponding target genes in uterine infection and the immune response. Viral proliferation in cells triggers immediate (innate) and delayed (adaptive) immune responses [41,42]. In this study, many proven immune genes were identified, such as the cytokines, IL-1β and IL-6, and the chemokines, CCL5 and CCL2 [43].…”
Section: Discussionmentioning
confidence: 90%
“…We next explored the role of these seven lncRNAs and their corresponding target genes in uterine infection and the immune response. Viral proliferation in cells triggers immediate (innate) and delayed (adaptive) immune responses [41,42]. In this study, many proven immune genes were identified, such as the cytokines, IL-1β and IL-6, and the chemokines, CCL5 and CCL2 [43].…”
Section: Discussionmentioning
confidence: 90%
“… 39 , 42 , 43 NF-kB-dependent upregulation of proapoptotic proteins Noxa and Puma also is required for efficient apoptosis induction. 44 , 45 Expression of the tumor suppressor protein p53 is increased in the brain during reovirus infection of neonatal mice, suggesting that reovirus also can induce p53-dependent cell death. 46 …”
Section: Innate Immune Responses To Reovirus Infectionmentioning
confidence: 99%
“…NF-κB inhibition, in turn, resulted in oncolytic protection and downregulation of p53-upregulated modulator of apoptosis (PUMA) expression. This study suggests that in breast cancer therapy, NF-κB acts proapoptotically, mediates RV-induced oncolysis, and may serve as a predictive indicator of the sensitivity to RV treatment [ 108 ].…”
Section: Ovs and Nf-κbmentioning
confidence: 99%